A computational study on the N-heterocyclic carbene-catalyzed Csp2–Csp3 bond activation/[4+2] cycloaddition cascade reaction of cyclobutenones with imines: a new application of the conservation principle of molecular orbital symmetry. Issue 29 (11th July 2016) - Wang, Yang; Wu, Bohua; Zhang, Haoyang; Wei, Donghui; Tang, Mingsheng
Abstract : A new application of the conservation principle of molecular orbital symmetry has been suggested for disclosing the role of NHC. Abstract : A comprehensive density functional theory (DFT) investigation has been performed to interrogate the mechanisms and stereoselectivities of the Csp 2 –Csp 3 single bond activation of cyclobutenones and their [4+2] cycloaddition reaction with imines via N-heterocyclic carbene (NHC) organocatalysis. According to our calculated results, the fundamental reaction pathway contains four steps: nucleophilic addition of NHC to cyclobutenone, C–C bond cleavage for the formation of an enolate intermediate, [4+2] cycloaddition of the enolate intermediate with isatin imine, and the elimination of the NHC catalyst. In addition, the calculated results also reveal that the second reaction step is the rate-determining step, whereas the third step is the regio- and stereo-selectivity determining step. For the regio- and stereo-selectivity determining step, all four possible attack modes were considered. The addition of the CN bond in isatin imine to the dienolate intermediate is more energy favorable than the addition of the CO bond to a dienolate intermediate. Moreover, the Re face addition of the CN bond in isatin imine to the Re face of the dienolate intermediate leading to the SS configuration N-containing product was demonstrated to be most energy favorable, which is mainly due to the stronger second-order perturbation energy value in the corresponding transition state. Furthermore, by tracking the frontier molecular orbital (FMO) changes in the rate-determining C–C bond cleavage step, we found that the reaction obeys the conservation principle of molecular orbital symmetry. We believe that the present work would provide valuable insights into this kind of reaction.